Giant esophageal diverticulum with stenosis treated with mediastinoscopic esophagectomy: A case report. (2020) - Tsuji, Toshikatsu; Saito, Hiroshi; Hayashi, Kengo; Kadoya, Shinichi; Bando, Hiroyuki
Highlights: An esophageal diverticulum is a rare condition. Laparoscopic diverticulectomy with myotomy and fundoplication for an esophageal diverticulum is the common approach. Mediastinoscopic esophagectomy for the patient who need esophagectomy could be an effective and noninvasive candidate procedure. Abstract: Introduction: An esophageal diverticulum is a rare condition, and surgery is indicated if symptomatic. We successfully performed mediastinoscopic esophagectomy for a giant esophageal diverticulum with stenosis. Presentation of case: A 63-year-old man visited our hospital because of dysphagia. He had been pointed out an esophageal diverticulum at a local hospital 13 years before visiting our hospital. Upper gastrointestinal endoscopy revealed an esophageal diverticulum at the lower thoracic esophagus and the structural stenosis in the anal side of the diverticulum. Computed tomography showed a 54 mm esophageal diverticulum at the lower thoracic esophagus. Esophagectomy was required because of the structural stenosis. His medical history included chronic obstructive pulmonary disorder. So, we chose the mediastinal approach to avoid a respiratory complication. We performed mediastinoscopic esophagectomy and esophagogastrostomy via the retrosternal route. The postoperative course was good. At 9 months postoperation, there were no symptoms. Discussion: Recently, laparoscopic diverticulectomy with myotomy and fundoplication has been considered the best approach in most cases. In the case with the structural stenosis, esophagectomy may be required. Conclusion: Mediastinoscopic esophagectomy for the patient with poor respiratory function and who need esophagectomy could be an effective and noninvasive candidate procedure.